PERBANDINGAN PEMBUKTIAN ACTUS REUS DAN MENS REA PADA TINDAKAN PERCOBAAN PERANTARA DALAM TRANSAKSI NARKOTIKA GOLONGAN 1 - Charlita Ratna Puteri Afrianda; Miko Aditiya Suharto (Universitas Labuhanbatu, 2026)
The increasingly rampant narcotics crimes in Indonesia pose a serious threat to public order and security. This study aims to analyze and compare the evidence of actus reus and mens rea in cases of attempted intermediary transactions of Class I narcotics based on Decision Number 572/Pid.Sus/2014/PN.Jkt.Utr and Decision Number 163/Pid.Sus/2015/PN.Mam. By using normative juridical research methods through case, comparative, statutory, and conceptual approaches, this study found fundamental differences in the judge's approach. In Decision 572/Pid.Sus/2014/PN.Jkt.Utr, the judge placed more emphasis on non-juridical considerations such as the social conditions and background of the defendant which resulted in an acquittal, even though when viewed from the elements of the attempt in Article 53 Paragraph (1) it had been fulfilled. In contrast, in Decision Number 163/Pid.Sus/2015/PN.Mam, the judge prioritized legal considerations based on evidence, while still considering the principle of the child's best interests, thus imposing a correctional measure. This research emphasizes the need for consistent standards of consideration to maintain legal certainty.Keywords: Comparison; Evidence; Drug Intermediary Trial